High-load full-color transparent display film as well as preparation method and application thereof

By using lanthanide fluoride nanocrystals and polyvinyl alcohol matrix in transparent display film, combining sandwich structure and epoxy resin photoblocking layer, the problems of low loading of phosphors and color crosstalk in existing transparent display technology are solved, and efficient and dynamic full-color transparent display effect is achieved.

CN119659132AActive Publication Date: 2025-03-21UNIV OF JINAN
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411719390.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-21
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

In the existing transparent display technology, the low load of the phosphor leads to insufficient luminescence intensity, and the lower transfer luminescence technology has color crosstalk problems, making it difficult to prepare a full-color transparent screen.

Method used

Lanthanide fluoride nanocrystals are used as emitters, and the color is adjusted by selecting doping activators, and the nanocrystals are embedded in the polyvinyl alcohol matrix to form a high-load full-color transparent display film. The display film adopts a sandwich structure, the middle layer is epoxy resin as the near-ultraviolet light blocking layer, and the two outer layers are red, green and blue light emitting layers, which are excited by different excitation sources to achieve independent excitation and reduce crosstalk.

Benefits of technology

It realizes the use of high-load nanocrystals, improves luminous intensity and transparency, solves the color crosstalk problem, and can realize dynamic full-color display on advanced displays, covering 40% of the NTSC color gamut area.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119659132A_ABST
    Figure CN119659132A_ABST
Patent Text Reader

Abstract

The invention discloses a high-load full-color transparent display film as well as a preparation method and application thereof, and belongs to the technical field of display screens. According to the invention, rare earth ions are selectively doped to obtain the green light, red light and blue light emitting nanocrystalline colloid. The structure of the light-emitting film is reasonably designed, and the epoxy resin layer, namely the near ultraviolet light blocking layer, is added between the light-emitting layers on the two sides, so that the light-emitting film of a sandwich structure is formed, and color crosstalk of transfer emission under red light and green light is inhibited. The problem that a down-transfer light-emitting display screen can only emit monochromatic light for a long time is solved, the full-color transparent screen is prepared, the load rate of the light-emitting material is remarkably improved, and the method has important economic value and social benefit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of display screens, and in particular to a high-load full-color transparent display film and a preparation method and application thereof. Background Art

[0002] With the rapid development of science and technology, various new display technologies are emerging. Among them, transparent display is gradually becoming an important development direction of future display technology with its unique advantages. Transparent display technology can display images on transparent media while maintaining the perspective of the scene behind it. It has a strong sense of technology, spatial awareness and interactivity, bringing unprecedented convenience to people's lives and work, such as: (1) augmented reality (AR) glasses: (2) augmented reality head-up display (AR-HUD): (3) commercial retail windows, interior decoration, building facades, etc. Transparent displays play a vital role in these applications, providing innovative and interactive experiences.

[0003] At present, mature transparent displays are electroluminescent screens, including light-emitting diodes (LEDs) and organic light-emitting diodes (OLED) screens. Both of these belong to electroluminescent display screens, which are composed of many tiny LED lamp beads arranged to form a large display panel, and form a color image through a combination of monochrome emitters. In order to meet the requirements of both achieving a certain luminous brightness and making the display screen transparent under sunlight, micro-LED lamp beads or OLED pixels are arranged at large intervals on a transparent substrate, which will affect the resolution of the screen. Based on this shortcoming, we can improve this shortcoming by preparing a full-color photoluminescent transparent display.

[0004] Photoluminescence technology includes upconversion luminescence and downconversion luminescence. For example, the paper "Orthogonal R / G / B Upconversion Luminescence-based Full-Color Tunable Upconversion Nanophosphors for Transparent Displays" (DOI: 10.1021 / acs.nanolett.1c01510) reports a LiReF-based 4Upconversion nanocrystals composed of a blue emitting core, a green emitting inner layer, a red emitting outer layer and several inert passivating shell layers. The nanocrystals were mixed with polydimethylsiloxane (PDMS) polymer to prepare a transparent screen, which achieved R / G / B orthogonal full-color luminescence at wavelengths of 1532, 800 and 980nm, respectively. However, the cumbersome synthesis process, low quantum efficiency, and excitation source focusing of multi-shell upconversion nanocrystals have hindered their practical application. To avoid these problems, the paper "Shining Transparent Displays with Stable Narrow-Band Blue-Emitting Phosphor in Layered Film" (10.1002 / adma.202206278) used NaLi 3 SiO 4 :Eu 2+ and K 2 SiF 6 :Mn 4+ High-efficiency down-conversion luminescent phosphors such as PDMS and PDMS are mixed with transparent polymers to form a display screen that displays a large color gamut and wide viewing angle. However, the transparent screen phosphor loading is only 1wt%. When the phosphor content increases to 2wt%, the transparency of the screen is greatly impaired, and a trade-off needs to be made between transmittance and luminescence intensity. In the paper "High-resolution X-ray luminescence extension imaging", the transparent screen phosphor loading is increased, but it can only reach 2.5wt%, that is, the low luminescence intensity caused by the low phosphor loading is common. In addition, crosstalk between different phosphors is also a problem that plagues down-transfer luminescence: for electroluminescence, its full-color fluorescent screen is a micron-sized three-primary color (red, green, and blue) LED lamp beads arranged in sequence on a transparent substrate. Each lamp bead can be individually controlled by current to control the luminescent color, solving the problem of crosstalk; for up-conversion luminescence, the core-multi-shell photoluminescence full-color fluorescent screen solves the problem of crosstalk by orthogonally exciting characteristic rare earth ions with excitation light; for down-transfer luminescence, although orthogonal excitation can also be tried, down-transfer excitation often results in overlapping excitation spectra between different doped ions, causing R / G / B emitters to interfere with each other under ultraviolet excitation, affecting color presentation. Therefore, the screen prepared by down-transfer luminescence can only achieve the effect of a monochrome display, but cannot achieve the preparation of a full-color transparent screen. Summary of the invention

[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide a high-load full-color transparent display film and a preparation method and application thereof.

[0006] The present invention proposes a material, design and method for realizing full-color transparent display. The developed display includes an excitation light source, a visible transparent display screen containing fluorescent materials and an optical lens. Once the transparent screen is illuminated, the excitation light will be converted into red, green or blue emission. The excitation light beam is patterned according to the shape on the mask plate, and finally a full-color image is generated on the transparent display screen.

[0007] Lanthanide fluoride nanocrystals are used as emitters by selective doping activators, including Tb 3+ ,Eu 3+ and Tm 3+ Secondly, we used polyvinyl alcohol (PVA) as the matrix, which has a similar refractive index to the nanocrystals, and achieved a transparency of up to 86% in the visible region at a high loading content of nanocrystals (80 wt%).

[0008] In order to reduce Tb 3+ and Eu 3+ To reduce the crosstalk between the emission of the ions, we embedded the nanocrystals into separate layers and then achieved independent excitation of the green and red layers by combining them with a UV selective absorber (epoxy resin). To display full-color luminescence in a transparent display, we will dope Yb 3+ and Tm 3+ The blue emission upconversion fluoride (NaYF 4 ) nanoparticles are embedded in the green emission layer, or the red emission layer. This is because the red and green down-transferred luminescent nanoparticles cannot be excited by the 980nm laser, so the blue light emitter does not need to be embedded in a new layer separately. At this time, the transparent film with a sandwich structure can emit red, green, and blue light (i.e. RGB) under the excitation of 395nm, 254nm and 980nm, respectively, and covers 40% of the NTSC color gamut area, showing good color rendering ability. To this end, we built a full-color transparent display prototype, which can display any designed pattern in real time in RGB mode under ambient light conditions. Full-color display with high transparency is achieved.

[0009] To achieve the above object, the present invention adopts the following technical solution:

[0010] The first aspect of the present invention provides a high-load full-color transparent display film, which includes a near-ultraviolet light blocking layer located in the middle and light-emitting layers tightly attached to both sides thereof; the light-emitting layers include a first light-emitting layer and a second light-emitting layer; the first light-emitting layer includes a red light-emitting material, and the second light-emitting layer includes a green light-emitting material; and the blue light-emitting material is located in at least one of the first light-emitting layer or the second light-emitting layer.

[0011] Furthermore, the near-ultraviolet light blocking layer includes epoxy resin, and the luminescent layer also includes polyvinyl alcohol.

[0012] Furthermore, the green light emitting material is a green light emitting nanocrystal colloid, and the green light emitting nanocrystal colloid includes Gd 3+ 、Ce 3+ , Tb 3+ Lanthanide fluoride nanocrystals;

[0013] The red light emitting material is a red light emitting nanocrystal colloid, and the red light emitting nanocrystal colloid includes Gd 3+ 、Ce 3+ 、Eu 3+ Lanthanide fluoride nanocrystals;

[0014] The blue light emitting material is a blue light emitting nanocrystal colloid, and the blue light emitting nanocrystal colloid includes Yb 3+ 、Tm 3+ Lanthanide fluoride nanocrystals.

[0015] Furthermore, the Gd-containing 3+ 、Ce 3+ , Tb 3+ Lanthanide fluoride nanocrystals containing 10-50% Gd 3+ 、1-20% Ce 3+ and 1-20% Tb 3+ NaYF 4 , red light emitting nanocrystal colloids containing 10-50% Gd 3+ 1-20% Ce 3+ and 1-20% Eu 3+ NaYF 4 The blue light emitting nanocrystal colloid contains 20-80% Yb 3+ and 0.1-10% Tm 3+ NaYF 4 .

[0016] Furthermore, the thickness of the near-ultraviolet light blocking layer is 1-300 μm, and the thickness of the luminescent layer is 1-300 μm; in the luminescent layer, the loading rate of the nanocrystals is 1-90 wt%.

[0017] The second aspect of the present invention provides a method for preparing the high-load full-color transparent display film, comprising the following steps:

[0018] (1) injecting a mixture consisting of polyvinyl alcohol and a luminescent material into a mold to form a first luminescent layer;

[0019] (2) After the first luminescent layer is dried, a layer of epoxy resin is added thereon to serve as a near-ultraviolet light blocking layer;

[0020] (3) After the near-ultraviolet light blocking layer is dried, a mixture of polyvinyl alcohol and a luminescent material is added thereon as a second luminescent layer, and after drying and shaping, a high-load full-color transparent display film is obtained.

[0021] Furthermore, the mass ratio of polyvinyl alcohol to the luminescent material is 1:(0.1-10); the degree of polymerization of polyvinyl alcohol is 100-10000.

[0022] Furthermore, the luminescent material has a length of 10-900 nm, a width of 1-100 nm, and a concentration of 0.01-1 g / mL.

[0023] The third aspect of the present invention provides a full-color transparent display device, comprising the high-load full-color transparent display film.

[0024] Furthermore, it also includes an excitation light source, and the wavelength of the excitation light source is 254nm, 395nm and 980nm.

[0025] Beneficial effects of the present invention:

[0026] The present invention obtains green, red and blue light emitting nanocrystalline colloids by selectively doping rare earth ions. By rationally designing the structure of the luminescent film, an epoxy resin layer, i.e., a near-ultraviolet light blocking layer, is added between the luminescent layers on both sides to form a high-load full-color transparent display film with a sandwich structure, which suppresses the color crosstalk of the red and green down-conversion emission. The present invention solves the long-standing problem that down-conversion luminescent displays can only emit monochromatic light.

[0027] After testing, the high-load full-color transparent display film prepared by the present invention has a thickness of less than 160μm, in which the loading amount of nanocrystals reaches 80wt%, far exceeding the level of 1-2.5wt% nanocrystal loading amount of the existing full-color screen film, and has high luminous intensity; at the same time, the transmittance of the high-load full-color transparent display film of the present invention is as high as 86%, and there is no need to trade off between transmittance and luminous intensity, which solves the problem that the transparency of the screen is damaged under high nanocrystal loading. Further, the prepared high-load full-color transparent display film is tested for flexibility, dynamic movement and different excitation sources. The results show that the high-load full-color transparent display film shows strong flexibility after 3000 mechanical bending cycles, while maintaining 90% of the initial photoluminescence intensity, showing reasonable application potential in advanced displays; the high-load full-color transparent display film can also achieve dynamic display, and the luminous color can cover 40% of the NTSC area. The high-load full-color transparent display film and full-color transparent screen prepared by the present invention have important economic value and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is an electron microscope photo of nanocrystals. Figure 1 Middle a, Figure 1 Medium b and Figure 1 In the middle, c represents green, red and blue light nanocrystals respectively.

[0029] Figure 2 These are photos of different drying times during the preparation of transparent luminescent films.

[0030] Figure 3 It is the thermogravimetric analysis curve of a single-color transparent film.

[0031] Figure 4 It is a wide-view, large-angle luminous photograph of a monochrome transparent film.

[0032] Figure 5 This is the XRD spectrum of the high-load full-color transparent display film.

[0033] Figure 6 It is the transmission spectrum of high-load full-color transparent display film.

[0034] Figure 7 These are the emission spectra of monochrome transparent films with different nanocrystal loading contents and photos of the corresponding films under sunlight and ultraviolet light excitation. From left to right in the photos are monochrome transparent films with loading amounts of 0%, 20%, 40%, 60%, 80%, and 90%.

[0035] Figure 8 It is a flexibility test of high-load full-color transparent display films. Figure 8 Middle A, Figure 8 Medium B and Figure 8 C in the middle represents emission spectrum, number of bends, and testing instrument.

[0036] Fig. 9 It is a dynamic multi-color display photo of the three primary colors of red (R), green (G), and blue (B).

[0037] Fig.10 This is a multicolor luminescence photograph of a high-load full-color transparent display film that uses a combination of 254nm, 395nm and 980nm wavelengths for excitation.

[0038] Fig.11 This is a prototype of a multi-color luminous transparent display prepared by the present invention. Three patterned excitation light beams are formed at 254nm, 395nm and 980nm through pattern masks of letters "J", "N" and "●", and then projected onto an imaging display under ambient light.

[0039] Fig.12 The luminous color of the high-load full-color transparent display film can cover the NTSC area. DETAILED DESCRIPTION

[0040] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0041] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0042] The experimental materials used in the embodiments of the present invention that are not specifically described are all conventional experimental materials in the field and can be purchased through commercial channels. The degree of polymerization of the polyvinyl alcohol (PVA) used in the present invention is 1700; the epoxy resin used in the present invention is purchased from Shenzhen Huasheng Tongchuang Technology Co., Ltd., and the model is HASUNCAST 3016LV PT-A&B potting glue.

[0043] The present invention is further described in detail below in conjunction with specific implementation methods. The present invention relates to a design and method for achieving full-color transparent display, including transparent film preparation, design and full-color display technology. The first part involves the selection of fluorescent materials, batch preparation and selection of film substrates, which are important conditions for the film to achieve transparency. We first selected lanthanide fluoride (NaYF4) as the luminophore because it has a wide band gap and high visible light transparency. The nanocrystals are synthesized by a hydrothermal method with oleic acid, ethanol and water as solvents. The synthesized precursor solution is transferred to a polytetrafluoroethylene-lined reactor, and the reactor is then sealed in a stainless steel housing, heated and naturally cooled to room temperature. The nanocrystals are washed and dispersed to obtain a uniform and stable colloid.

[0044] Regarding the choice of film substrate, the choice of substrate is first related to the effective refractive index difference. The smaller the refractive index difference, the smaller the scattering and the higher the transparency (effective refractive index: 1.464, refractive index of polyvinyl alcohol: 1.48). Secondly, it is related to whether the polymer is water-soluble, because the phosphor is dispersible in water. Polymers with too large a refractive index difference and non-water-soluble polymers do not meet the conditions. Therefore, polyvinyl alcohol (PVA) was finally selected as the substrate material.

[0045] The synthesized nanocrystal colloid was mixed evenly with a PVA aqueous solution with a concentration of 50 mg / mL in a mass ratio of 4:1, and then dropped on a watch glass. After drying naturally at room temperature for 3 hours, a transparent flexible luminescent film was obtained. However, the flexible luminescent film is still a monochrome luminescent film, that is, the prepared luminescent film can only emit one kind of light (red, green or blue light), which is equivalent to embedding only one kind of luminescent nanoparticles in the film. We further improved and designed the monochrome luminescent film and prepared a full-color film, that is, the prepared luminescent film contains nanoparticles of at least three basic luminescent colors (red, green and blue). The three luminescent nanoparticles can be excited at the same time, and the three colors of light with different intensities are mixed by adjusting the corresponding excitation light intensity to achieve full-color display.

[0046] The high-load full-color transparent display film prepared by the present invention is a sandwich structure: the two outer layers are light-emitting layers, and the middle layer is an epoxy resin layer. After the first red light-emitting layer is dried, a layer of epoxy resin is dripped on the basis thereof, and dried at 80°C for 6 hours. On this basis, green and blue light-emitting nanocrystal colloids are mixed in proportion and dripped on the epoxy resin layer, and dried again to obtain the second light-emitting layer. The sandwich structure film is peeled off from the culture dish to obtain a flexible high-load full-color transparent display film.

[0047] To this end, we built a full-color transparent display prototype that can display any designed pattern in real time in RGB mode under ambient light conditions. The display device constructed consists of 395 and 254-nm LED flashlights, a 980-nm laser, two biconvex lenses, two pattern masks, and a high-load full-color transparent display film. The 395 and 254-nm LED flashlights are respectively irradiated on both sides of the transparent display film. The pattern mask and biconvex lenses are placed in front of the flashlights in sequence. The excitation light passes through the mask and the biconvex lenses, and finally the inverted and magnified patterned excitation light is irradiated onto the transparent display film to obtain a full-color display pattern. It is worth noting that the full-color transparent display can be seen at any angle and has the characteristics of wide viewing angle display.

[0048] Example 1: Preparation of Nanocrystalline Colloid

[0049] The present invention firstly prepares green light emitting nanocrystalline colloids and red light emitting nanocrystalline colloids. The synthesis method refers to the reference "Flexible and Transparent Ceramic Nanocomposite for Laboratory X-ray Imaging of Micrometer Resolution" (DOI: 10.1021 / acsnano.2c10531), and the doping elements and proportions are determined by the reference "Synthesis of multifarious hierarchical flower-like NiO and their gas-sensingproperties" (DOI: 10.1016 / j.materresbull.2013.04.014).

[0050] Preparation of green light-emitting nanocrystal colloids

[0051] The green light emitting nanocrystal colloid used in the present invention is NaYF 4 :30% Gd 3+ , 5% Ce 3+ , 5% Tb 3+ The nanocrystals are synthesized by hydrothermal method, and the specific synthesis steps are as follows:

[0052] Weigh a certain mass of rare earth metal chloride, GdCl 3 6H 2 O, YCl 3 6H 2 O、CeCl 3 7H 2 O and TbCl 3 6H 2 O totaling 8 mol; the ratio of the four raw materials is 3:6:0.5:0.5. Add the above chlorides to 8 mL of deionized water, stir ultrasonically to dissolve and set aside. First, add 160 mL of oleic acid and 80 mL of anhydrous ethanol to a 500 mL beaker, and stir at room temperature for 5 minutes to mix them evenly. Then dissolve 9.6 g of NaOH in 16 mL of deionized water, stir ultrasonically to completely dissolve it, add the NaOH solution dropwise to the mixed solution of oleic acid and ethanol, and stir at 100 ° C to completely dissolve it. Then add the rare earth metal chloride aqueous solution and 64 mL of NH 4F (1mol / L) aqueous solution, the solution turned milky white, continued stirring for 10min and then transferred to a 500mL hydrothermal reactor, reacted at 200℃ for 6h, and then naturally cooled to room temperature. Finally, centrifuged at 8000rpm for 5min, the white precipitate was washed once with cyclohexane and anhydrous ethanol at a volume ratio of 1:1, and then washed 3 times with 2mol / L HCl solution and anhydrous ethanol at a volume ratio of 1:1. The final product was dispersed in 8mL deionized water to obtain stable green light emitting nanocrystalline colloid NaYF 4 :30% Gd 3+ , 5% Ce 3+ , 5% Tb 3+ , electron microscope photos see Figure 1 Middle a.

[0053] Preparation of red light-emitting nanocrystal colloids

[0054] The red light emitting nanocrystal colloid used in the present invention is NaYF 4 :30% Gd 3+ , 5% Ce 3+ , 5% Eu 3+ The nanocrystals were synthesized by hydrothermal method, which is different from the above-mentioned green light emitting nanocrystal colloidal synthesis method in that EuCl 3 6H 2 O replaces TbCl 3 6H 2 O, the rest are the same, electron microscope photos see Figure 1 Middle b.

[0055] The present invention then prepared blue light emitting nanocrystal colloids. The synthesis method was based on the reference "Flexible and Transparent Ceramic Nanocomposite for Laboratory X-ray Imaging of Micrometer Resolution" (DOI: 10.1021 / acsnano.2c10531), and the doping elements and proportions were determined by the reference "Preparation of core-shell NaGdF4 nanoparticles doped with luminescent lanthanide ions to be used as upconversion-based probes" (DOI: 10.1038 / nprot.2014.111).

[0056] Preparation of blue light-emitting nanocrystal colloids

[0057] For blue light emission, the blue light emitting nanocrystal colloid used in the present invention is NaYF 4 :49% Yb 3+ , 1% Tm 3+ @NaYF 4 , using the solvothermal method for synthesis, the specific synthesis steps are as follows:

[0058] First, the nanocrystalline core NaYF 4 :49% Yb 3+ ,1% Tm 3+ :6.4mmol RE(Ac) 3 (RE = Y, Yb and Tm) was added to a 100 mL flask containing 12 mL oleic acid and 28 mL 1-octadecene. The solution was heated to 150 ° C under vacuum degassing conditions and stirred vigorously for 1 hour to form a transparent lanthanum oleate precursor, which was naturally cooled to room temperature. Subsequently, 16 mmol of sodium oleate solid was added to the precursor, and the solution was heated to 100 ° C under vacuum degassing conditions and stirred vigorously for 1 hour. Then, 25.6 mmol of NH 4 F powder was vacuum degassed at 160°C for 1 hour, then switched to nitrogen atmosphere, and the reaction mixture was heated to 300°C, stirred stably for 1.5 hours, and cooled naturally to room temperature. The product was transferred to a centrifuge tube and collected by centrifugation at 8000rpm for 5 minutes. The white precipitate was washed once with cyclohexane and anhydrous ethanol in a volume ratio of 1:1, and then washed three times with 2mol / L HCl solution and anhydrous ethanol in a volume ratio of 1:1. The final product was dispersed in 8mL of deionized water to obtain a stable blue light emitting nanocrystal colloid. The electron microscope photo is shown in Figure 1 Middle c.

[0059] Example 2: Preparation of transparent film

[0060] Preparation of transparent films with red light-emitting nanocrystals as luminescent bodies:

[0061] (1) First, the NaYF synthesized in Example 1 4 :30% Gd 3+ , 5% Ce 3+ , 5% Eu 3+ The nanocrystal colloid is quantified. After determining the weight of a 2mL plastic centrifuge tube, 200μL is measured from the 8mL colloidal solution into a centrifuge tube and placed in a 60℃ oven to dry until all the water evaporates. Then it is weighed again, and the weight of the 200μL nanocrystal is obtained by subtracting the first weight from the second weight. At this point, the content and concentration of the nanocrystals in the remaining 7.8mL colloid can be calculated.

[0062] (2) Polyvinyl alcohol (PVA) was selected as the supporting matrix, and PVA powder was added into deionized water. The mixture was stirred at 90° C. for two days until the solid powder was completely dissolved, thereby obtaining a 50 mg / L PVA aqueous solution.

[0063] (3) Then, the nano-colloid and PVA aqueous solution are mixed evenly according to the weight ratio of nano-crystals: polyvinyl alcohol = 4g: 1g powder glue, and the mixture is dripped onto the plastic surface dish mold. Figure 2 As shown, after natural drying for 3 hours, as the water in the mixture evaporates, the film changes from opaque to transparent, and a transparent film that emits red light and is flexible is obtained.

[0064] The obtained film has a thickness of about 40 μm, a nanocrystal loading of 80%, and a transmittance as high as 86% as verified by an ultraviolet-visible spectrophotometer.

[0065] Preparation of transparent films with green light emitting nanocrystals as luminescent bodies:

[0066] The difference between this method and the preparation method of transparent thin film using red light emitting nanocrystals as luminescent bodies is that the green light emitting nanocrystal colloid NaYF 4 :30% Gd 3+ , 5% Ce 3+ , 5% Tb 3+ Replacement of red light emitting nanocrystalline colloidal NaYF 4 :30% Gd 3+ , 5% Ce 3+ , 5% Eu 3+ , and the rest are the same.

[0067] The final film thickness is about 40 μm, and the nanocrystal loading is 80%. Figure 3 The UV-visible spectrophotometer verifies that the transmittance is as high as 86%.

[0068] Example 3: Construction of wide viewing angle luminous display

[0069] Taking the green light emitting transparent film as an example, we designed a wide-viewing angle luminous display prototype. The transparent film is fixed in a position, and the double convex lens, pattern mask and 254nm light source are placed in front of the film at an appropriate distance. The excitation light from the mask passes through the double convex lens and converges on the transparent film, thereby stimulating green light with a pattern. At this time, we use a camera to circle the transparent film and take luminous photos of the transparent film every 30°.

[0070] The results are as follows Figure 4 As shown, the transparent film can well display clear luminescence at different angles, indicating that the transparent film has the potential for wide-viewing angle luminescence display.

[0071] Example 4: Construction of a high-load full-color transparent display film

[0072] Because Ce 3+ For the 4f-5d transition of ions, both red and green emitting transparent films have a wide excitation peak at 254nm. In addition, the red emitting transparent film has an additional Eu at 395nm. 3+ Based on this, we can use different excitation sources for the red and green light-emitting films for selective excitation: the green light-emitting film is excited by a 254nm ultraviolet lamp, while the red light-emitting film is excited by a 395nm lamp.

[0073] However, there is a problem. The 254nm ultraviolet light can not only excite the green light emitting film, but also the red light emitting film, which will cause color crosstalk between the red and green lights.

[0074] In order to solve this problem, we designed a multi-layer transparent film with a sandwich structure. We chose a transparent glue and epoxy resin that can absorb near-ultraviolet light to stick the red and green light emitting films together. The sandwich structure has three layers in total. The middle layer is the epoxy resin layer, which is the near-ultraviolet light blocking layer. The two outer layers are the red and green light emitting layers. When the 254nm ultraviolet lamp irradiates the green light emitting layer, the sandwich film emits green light as a whole, because the 254nm light can only excite the green light layer. The red light layer on the other side will not be excited by the 254nm lamp because the excitation light is absorbed by the middle layer of epoxy resin, and almost no 254nm light reaches the red light layer. For the red light film, we use 395nm lamp to excite. Whether it is excited on the green light film side or the red light film side, it can only excite Eu. 3+ ions, making the sandwich membrane emit red light, achieving asymmetric red and green multicolor emission.

[0075] Since we have achieved independent excitation of the green and red layers, the only missing primary color is blue. In order to display full-color luminescence in a transparent display, the blue-light emitting upconversion nanoparticles NaYF prepared in Example 1 were used. 4 :49%Yb 3 + , 1% Tm 3+ @NaYF 4 The nanoparticles have a diameter of 11.5nm and emit blue light under 980nm laser excitation. Since both red and green down-conversion nanoparticles are inactive under 980nm laser excitation, the blue luminescent nanoparticles can be embedded in the green or red emission layer (in this experiment, the green emission layer) instead of in a new layer of PVA film. In this way, the sandwich film can emit red, green, and blue light (i.e., RGB) under excitation at 395nm, 254nm, and 980nm, respectively.

[0076] The specific preparation method of the high-load full-color transparent display film of the sandwich structure is as follows:

[0077] The high-load full-color transparent display film prepared by the present invention is a sandwich structure: the two outer layers are light-emitting layers, and the middle layer is an epoxy resin layer. After the first red light-emitting layer is dried, a layer of epoxy resin is dripped on the basis thereof, and dried at 80°C for 6 hours. On this basis, green and blue light-emitting nanocrystal colloids are mixed in proportion and dripped on the epoxy resin layer, and dried again to obtain the second light-emitting layer. The sandwich structure film is peeled off from the culture dish to obtain a flexible high-load full-color transparent display film.

[0078] The preparation method of the first red light emitting layer is the same as the preparation method of the transparent film using red light emitting nanocrystals as the luminescent body in Example 2.

[0079] The preparation method of the second light-emitting layer is different from the preparation method of the transparent film using green light-emitting nanocrystals as the light-emitting body in Example 2 in that the green light-emitting nanocrystal colloid NaYF 4 :30% Gd 3+ , 5% Ce 3 + , 5% Tb 3+ and blue light emitting upconversion nanoparticles NaYF 4 :49% Yb 3+ , 1% Tm 3+ @NaYF 4 Instead of using only green light-emitting nanocrystal colloidal NaYF 4 :30% Gd 3+ , 5% Ce 3+ , 5% Tb 3+ The weight ratio of the green light emitting nanocrystal colloid to the blue light emitting upconversion nanoparticles is 1:1.

[0080] This time, a 3cm diameter plastic petri dish was used as a template. The loading amount of nanocrystals in the two luminescent layers was 0.2g, the red light layer was 0.2g, and the green-blue light mixed layer was 0.2g, of which the blue and green light nanocrystals were 0.1g each. The thickness of the red light layer and the green-blue light mixed layer were 26μm and 28μm respectively; the thickness of the intermediate epoxy resin was 97μm.

[0081] The composition of the sandwich structured full-color transparent display film was analyzed by XRD, such as Figure 5 As shown in the figure, the diffraction peak intensity is high, indicating that the loaded nanocrystals have high crystallinity. The transmittance of the prepared sandwich structure full-color transparent display film in visible light was tested by UV-visible spectrophotometer. The results are as follows Figure 6As shown, the high-load full-color transparent display film achieved high transparency (T ~ 86%), indicating that the transparency of the film we prepared is very high.

[0082] Example 5: Testing of high-load full-color transparent display film

[0083] The high-load full-color transparent display film prepared in Example 4 was tested for luminous intensity, flexibility, dynamic movement and different excitation sources.

[0084] The detection results of luminescence intensity are as follows Figure 7 As shown in the figure, according to the emission spectra of monochromatic transparent films with different nanocrystal loading contents and the photos of the corresponding films under sunlight and UV light excitation, from left to right in the photos are monochromatic transparent films with loading contents of 0%, 20%, 40%, 60%, 80%, and 90%. The luminous intensity increases with the increase of phosphor loading content. The stronger the luminous intensity, the brighter the screen produced. Since the monochromatic transparent film will appear white and affect the transmittance in the case of 90% loading, the monochromatic transparent film with 80% loading is selected.

[0085] The flexibility test method is as follows: Figure 8 As shown in Figure c, the luminous transparent film is fixed on a linear actuator (an actuator that can produce motion in a straight line, as opposed to the circular motion of a traditional motor). After connecting to a power source, the linear actuator can automatically reciprocate to drive the film to bend. The film is excited by a 254nm ultraviolet lamp, and the luminous intensity of the film is monitored in real time using a fiber optic spectrometer.

[0086] according to Figure 8 A and Figure 8 Middle b, the high-load full-color transparent display film shows strong flexibility after 3000 mechanical bending cycles while maintaining 90% of the initial photoluminescence intensity, demonstrating reasonable application potential in advanced displays.

[0087] Fig. 9 The dynamic movement test results are shown in the dynamic multi-color display photos of the three primary colors of red (R), green (G), and blue (B). The three color light spots can be moved dynamically and combined at the same position to obtain a white light spot. This shows that the high-load full-color transparent display film can also achieve dynamic display.

[0088] Fig.10 Test results for different excitation sources: The multi-color luminescence of the high-load full-color transparent display film is adjusted by combining excitations of 254nm, 395nm and 980nm wavelengths. Under three different excitation sources (254, 395 and 980nm) and excitation intensities, the luminous intensities of the three colors are different, and the resulting mixed colors are also different, thus achieving full-color luminous display.

[0089] Example 6: Construction of a transparent full-color display prototype

[0090] This embodiment is to build a transparent full-color display prototype. The self-made prototype consists of three excitation sources (254, 395nm ultraviolet lamps and 980nm laser), two pattern masks "J" and "N", two double convex lenses and the high-load full-color transparent display film prepared in Example 4.

[0091] The results are as follows Fig.11 As shown, the high-load full-color transparent display film displays a “J●N” pattern under ambient light conditions and can be clearly seen at a 4π viewing angle, thus realizing a patterned transparent full-color luminescent display.

[0092] Since RGB pixels are generated by focused excitation points, their movement is controlled by optical devices, in addition to RGB colors, when they overlap, a white light pixel is easily synthesized. In order to further test the color gamut of the high-load full-color transparent display film prepared by the present invention, by adjusting the excitation intensity of the RGB components, we plotted the full color gamut, and further compared the area of ​​the high-load full-color transparent display film prepared by the present invention (white solid line) with the NTSC area (black dotted line).

[0093] Results Fig.12 , through ratio calculation, it is obtained that the luminous color of the high-load full-color transparent display film can cover 40% of the NTSC area.

[0094] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A high-load full-color transparent display film, characterized in that: The high-load full-color transparent display film includes a near-ultraviolet light blocking layer located in the middle and light-emitting layers tightly attached to both sides thereof; the light-emitting layers include a first light-emitting layer and a second light-emitting layer; the first light-emitting layer includes a red light-emitting material, and the second light-emitting layer includes a green light-emitting material; the blue light-emitting material is located in at least one of the first light-emitting layer or the second light-emitting layer.

2. The high-load full-color transparent display film according to claim 1, characterized in that: The near-ultraviolet light blocking layer comprises epoxy resin, and the luminescent layer further comprises polyvinyl alcohol.

3. The high-load full-color transparent display film according to claim 2, characterized in that: The green light emitting material is a green light emitting nanocrystal colloid, and the green light emitting nanocrystal colloid includes Gd 3+ 、Ce 3+ , Tb 3+ Lanthanide fluoride nanocrystals; The red light emitting material is a red light emitting nanocrystal colloid, and the red light emitting nanocrystal colloid includes Gd 3+ 、Ce 3+ 、Eu 3+ Lanthanide fluoride nanocrystals; The blue light emitting material is a blue light emitting nanocrystal colloid, and the blue light emitting nanocrystal colloid includes Yb 3 + 、Tm 3+ Lanthanide fluoride nanocrystals.

4. The high-load full-color transparent display film according to claim 3, characterized in that: The Gd-containing 3+ 、Ce 3+ , Tb 3+ Lanthanide fluoride nanocrystals containing 10-50% Gd 3+ 1-20% Ce 3+ and 1-20% Tb 3+ NaYF4, red-emitting nanocrystal colloids containing 10-50% Gd 3+ 1-20% Ce 3+ and 1-20%Eu 3+ NaYF4, blue light emitting nanocrystal colloids containing 20-80% Yb 3+ and 0.1-10% Tm 3+ of NaYF4.

5. The high-load full-color transparent display film according to claim 1, characterized in that: The thickness of the near-ultraviolet light blocking layer is 1-300 μm, and the thickness of the luminescent layer is 1-300 μm; in the luminescent layer, the loading rate of the nanocrystals is 1-90 wt%.

6. The method for preparing a high-load full-color transparent display film according to any one of claims 1 to 5, characterized in that: The steps include: (1) injecting a mixture consisting of polyvinyl alcohol and a luminescent material into a mold to form a first luminescent layer; (2) After the first luminescent layer is dried, a layer of epoxy resin is added thereon to serve as a near-ultraviolet light blocking layer; (3) After the near-ultraviolet light blocking layer is dried, a mixture of polyvinyl alcohol and a luminescent material is added thereon as a second luminescent layer, and after drying and shaping, a high-load full-color transparent display film is obtained.

7. The method for preparing a high-load full-color transparent display film according to claim 6, characterized in that: The mass ratio of polyvinyl alcohol to the luminescent material is 1:(0.1-10); the polymerization degree of polyvinyl alcohol is 100-10000.

8. The method for preparing a high-load full-color transparent display film according to claim 6, characterized in that: The luminescent material has a length of 10-900 nm, a width of 1-100 nm, and a concentration of 0.01-1 g / mL.

9. A full-color transparent display device, characterized in that: The invention comprises the high-load full-color transparent display film as described in any one of claims 1 to 5.

10. The full-color transparent display device according to claim 9, characterized in that: The invention also comprises an excitation light source, wherein the wavelength of the excitation light source is 254 nm, 395 nm and 980 nm.

Citation Information

Patent Citations

  • Dual-mode orthogonal three-primary-color light-emitting nano particle, multi-stage anti-counterfeiting material and preparation method and application of multi-stage anti-counterfeiting material

    CN116103032A

  • Transparent colorful light-emitting projection display screen

    CN118112880A

  • Display device

    JP2011164537A